2018
DOI: 10.5194/amt-11-2821-2018
|View full text |Cite
|
Sign up to set email alerts
|

Folded tubular photometer for atmospheric measurements of NO<sub>2</sub> and NO

Abstract: Abstract. We describe and characterize a modular folded tubular photometer for making direct measurements of the concentrations of nitrogen dioxide (NO2) and specify how this method could be extended to measure other pollutants such as sulfur dioxide (SO2), ozone (O3), and black carbon particulate matter. Direct absorbance measurements using this photometer can be made across the spectral range from the ultraviolet (UV) to the near infrared. The absorbance cell makes use of modular components (tubular detectio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 38 publications
0
26
0
Order By: Relevance
“…The model 405 nm instrument measures NO 2 directly based on the absorbance at 405 nm, and NO is measured by adding excess O 3 (conversion efficiency ∼ 100 %). The limit of detection of both NO and NO 2 is 1 part per billion volume (ppbv), with an accuracy of 2 ppbv or 2 % of the reading, and the time resolution is 10 s (Birks et al, 2018). The model 106-L instrument measures O 3 based on the absorbance at 254 nm, with a precision of 1 ppbv, or 2 % of the reading, and a limit of detection of 3 ppbv.…”
Section: Field Measurementmentioning
confidence: 99%
“…The model 405 nm instrument measures NO 2 directly based on the absorbance at 405 nm, and NO is measured by adding excess O 3 (conversion efficiency ∼ 100 %). The limit of detection of both NO and NO 2 is 1 part per billion volume (ppbv), with an accuracy of 2 ppbv or 2 % of the reading, and the time resolution is 10 s (Birks et al, 2018). The model 106-L instrument measures O 3 based on the absorbance at 254 nm, with a precision of 1 ppbv, or 2 % of the reading, and a limit of detection of 3 ppbv.…”
Section: Field Measurementmentioning
confidence: 99%
“…However, the stand-alone ozone calibrator (Model 306) operates using rather different flow rates (and therefore, residence times) than the ozone photolysis cell in the NO2/NO/O3 calibrator described here. Birks et al (2018a) found that 500 chemical loss of ozone due to OH and HO2 radicals (generated either by water photolysis at 184.9 nm or by ozone photolysis and subsequent reaction of O( 1 D) with H2O) was a negligible effect on the ozone output in the stand-alone ozone calibrator (the Model 306). The only effect of water vapor was the small dilution of the O2 precursor by water vapor in the photolysis cell that results in a small of reduction of the ozone generated (up to ~2 %).…”
Section: Water Vapor Effects and Verification Of The Modified Photolymentioning
confidence: 99%
“…Therefore, for NO2-only analyzers the GPT calibration method requires either (1) a second 105 instrument that can measure the loss of NO or (2) a NIST-traceable ozone source, such that the loss of ozone can be correlated with the formation of NO2. Note that the standard GPT calibration procedures can still be applied to methods that directly measure NO2 and then indirectly measure NO (the opposite of the chemiluminescence technique) -such as in the long-path folded tubular photometer (FTP) developed in our group that measures direct NO2 absorbance at 405 nm (Birks et al, 2018a). 110…”
Section: Introductionmentioning
confidence: 99%
“…The fre-quency of calibration depends upon the species being measured and the instrumental approach. A detailed discussion of ozone detection methods and calibration protocols is given in a previous publication describing a portable ozone calibrator (Birks et al, 2018b) and will not be repeated here. In the past, NO x calibration methods were developed primarily for use with analyzers based on the chemiluminescence (CL) reaction of NO with an excess of ozone, which is the most widely used method for quantifying NO and, following its conversion to NO, NO 2 (Fontijn et al, 1970;Ridley and Howlett, 1974;Kley and McFarland, 1980;Steffenson and Stedman, 1974;Demerjian, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, for NO 2 -only analyzers the GPT calibration method requires either (1) a second instrument that can measure the loss of NO or (2) a NIST-traceable ozone source such that the loss of ozone can be correlated with the formation of NO 2 . Note that the standard GPT calibration procedures can still be applied to methods that directly measure NO 2 and then indirectly measure NO (the opposite of the chemiluminescence technique) -such as in the long-path folded tubular photometer (FTP) developed in our group that measures direct NO 2 absorbance at 405 nm (Birks et al, 2018a).…”
Section: Introductionmentioning
confidence: 99%